Smart Management And The Role Of Scientific Research In Achieving Sustainable Development, A Case Study Of Misurata University In Libya (Journal of Namibian Studies : History Politics Culture, 2023)
This study conducted at Misurata University in Libya aimed to explore the relationship between scientific research and implementing smart management practices for sustainable development. A total of 1236 teaching staff members from different departments and colleges participated in the study. Data was collected through 253 online surveys using the Smart. pls 4 program and analyzed using descriptive and inferential statistics. The study's results revealed a significant positive relationship between scientific research and implementing smart management practices at Misurata University. Furthermore, technology and data literacy strengthened this relationship and acted as moderators. Faculty members' perceptions of institutional support for research and development did not directly affect the relationship between scientific research and smart management practices. The results of this study contribute to the understanding of the role of scientific research in supporting smart management practices and can guide universities and organizations in formulating strategies for sustainable development. Further research is encouraged to explore the moderating effects of technology and data and the influence of institutional support in more depth.